Penerapan Model Pembelajaran Argument Driven Inquiry (ADI) Untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa Di Kelas X SMK Negeri 1 Angkola Timur - Layli Adha Siregar; Eni Sumanti Nasution; Sri Utami Khoilla Mora Siregar (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2023)
This study aims to determine the improvement of student learning outcomes by using the Argument Driven Inquiry (ADI) learning model. The sample of this study were sudents of class X TBSM with a total sampel of 36 people. This type of research is classroom action research. The analysis teachnique uses the average value. The conclusion of this study is that there is an increase in learning outcomes using the Argument Driven Inquiry learning model, this can be seen from an increase in the pre-cycle in terms of the average value of student learning outcomes, which is 31,42, increasing in the frist cycle to 55,27 and in the second cycle 85,82. And if viewed from the student’s completeness o btained from the precycle complete 2%, the first cycle 21% and the second cycle 85%.